There is No Free: An Indigenous Informed Perspective on Free, Prior and Informed Consent - Burns, Nicole (Scholars Commons @ Laurier, 2020)
Many Indigenous nations in Canada are faced with complex issues surrounding proposed development on their lands. There are numerous rights frameworks that support Indigenous Peoples’ inherent rights, which includes their right to free, prior and informed consent (FPIC) in relation to any development that would impact their lands. This case study examined the various perspectives of Matawa First Nations in regard to their experiences of consultation with government and industry. This study was conducted by performing document review and analysis of three focus groups (n=20), a video analysis of the APTN documentary series Ring of Fire and survey distribution and analysis (n=49). Results indicate that Matawa’s experience of the implementation of FPIC fails to comply with Indigenous laws and ideologies and is also not in keeping with the principles of FPIC itself. Government and industry exercise their power by creating biased laws, processes, and spaces for consultation and denying Matawa First Nations any means of participating except by those rules. Matawa First Nations have expressed their willingness to establish genuine relationships with government and industry and work towards sustainable development of their lands. This study ends with a list of recommendations for government and industry to consider in moving forward with consent-seeking in a way that is in keeping with Indigenous perspectives and the principles of FPIC.